Protective effects of curcumin on chromatin quality, sperm parameters, and apoptosis following testicular torsion-detorsion in mice - Shahedi, Abbas (Clin Exp Reprod Med, 2021)
OBJECTIVE: The chief outcome of testicular torsion in clinical and experimental contexts is testicular ischemia. Curcumin, a compound with anti-inflammatory and antioxidant properties, has fascinated researchers and clinicians for its promise in the treatment of fertility diseases. METHODS: Thirty-five fully grown male mice were randomly classified into five groups: control, sham, testicular torsion, treatment group 1 (testicular torsion+short-term curcumin), and treatment group 2 (testicular torsion+long-term curcumin). Thirty-five days later, spermatozoa from the right cauda epididymis were analyzed with regard to count and motility. Toluidine blue (TB), aniline blue (AB), and chromomycin A3 (CMA3) staining assays were used to evaluate the sperm chromatin integrity. In addition, the terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) test was used to assess apoptosis. RESULTS: Treatment group 1 exhibited a remarkably elevated sperm count compared to the testicular torsion group. Additionally, notably lower sperm motility was found in the testicular torsion group compared to the control, treatment 1, and treatment 2 groups. Staining (CMA3, AB, and TB) and the TUNEL test indicated significantly greater testicular torsion in the torsion group compared to the control group (p<0.05). The data also revealed notably lower results of all sperm chromatin assays and lower apoptosis in both treatment groups relative to the testicular torsion group (p<0.05). Significantly elevated (p<0.05) AB and TB results were noted in treatment group 1 compared to treatment group 2. CONCLUSION: Curcumin can compensate for the harmful effects of testicular ischemia and improve sperm chromatin quality in mice.